Hudūd dalam Al-Qur’an: Pembacaan Ulang Hermeneutik atas Hukuman Seratus Cambukan dalam QS. An-Nūr [24]: 2-3 - Nisrina Tuhfatul Azizha; Naqiyah Naqiyah (Contemporary Quran, 2025)
The Qur’ānic prescription of one-hundred lashes for fornication in QS An-Nūr 24:2–3 has long provoked tension between classical Islamic jurisprudence and contemporary human-rights norms. Existing commentary, dominated by fiqh-centric, atomistic readings, often neglects the socio-historical matrix that shaped the verse and, consequently, its moral telos. This study reinterprets the passage through Fazlur Rahman’s double-movement hermeneutic within a qualitative research design. Primary data comprise pre-Islamic records of flogging, early, medieval, and modern tafsīr, and statutory applications of ḥ udūd; secondary data derive from recent scholarship on Islamic criminal law and international human-rights law. The first hermeneutic movement reconstructs the historical landscape of corporal punishment from Ancient Rome to early Madīnah, revealing the lash as a socially intelligible deterrent rather than a sacralised ritual. The second movement distils a universal moral ideal—social protection through deterrence—and tests its compatibility with modern human-rights principles. Findings show that the ethical objective of An-Nūr 24:2–3 can be upheld today through non-violent, educational, and restorative measures that respect bodily integrity while preserving the Qur’ān’s preventive intent. The study thus offers a viable framework for reconciling Islamic normative authority with contemporary humanitarian standards